Pengaruh kualitas produk dan kualitas pelayanan terhadap kepuasan pelanggan produk chemical pada PT. XYZ - Nurlela, Ela (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
There are a number of factors that contribute to or detract from customer satisfaction; product and service quality are two of them. The purpose of this research is to analyze the relationship between PT. XYZ's chemical product quality and their customer service quality. 125 PT. XYZ clients meeting the study's age range of 26-50 years old made up the study's population. A total of 125 typical clients were surveyed. Descriptive and correlational methods are used in this study. Methods from the realm of quantitative analysis, include studies checking for validity and reliability, as well as other statistical tests like correlation, regression, and the coefficient of determination. T count > t table = 6.529 > 1.65744, which indicates a statistically significant relationship between product quality and satisfied customers. T count > t table = 9.444 > 1.65744 indicates a substantial relationship between service quality and customer satisfaction. With the regression equation Y = 3.130 + 0.550 X1 - 0.944 X2. + e, we find that product quality and service quality have a considerable impact on consumer satisfaction. Suggestions that can be used for the development of the company in the future, namely, to increase customer satisfaction, management must maximize product benefits to customers by increasing the standard of materials used. In terms of service quality, management needs to improve the quality of service to customers in order to give a good impression so that customers continue to trust in buying products.